Wartość czasu pracy w podmiotach leczniczych. Dylematy, uregulowania, społeczno-moralne implikacje - Prüfer, Paweł; Piszczygłowa, Bernadeta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
Time is a value in itself and a useful one. Medical entities use this value in many ways. The medical staff`s working time spent carrying out medical duty and rest periods are regulated by formal laws. The value of working time depends on the type of work, the entity that carries it out, as well as the cultural and social context. An important element determining the value of working time is ultimately the reference to the human being as the subject and priority of all social activities. This applies to the broadly understood good of doctors and patients. This is an ethical and axiological perspective that should not be overlooked in the functioning and management of medicinal entities.